Recursos naturais e sustentabilidade: a responsabilidade social, ambiental e jurídica das empresas - Burmann, Larissa Lauda (My University, 2014)
This study presents analysis and reflections about the integration of social responsibility on the concept of sustainable development which, in turn, is implicitly covered in the article 225 CF/88. It should be mentioned that the 1988 constituent listed in the article 225, caput, the balanced environment as a fundamental right, arising from the right to life itself, and forbided any activity that could potentially jeopardize that - good environmental protection. Thereby, the social responsibility taken by companies as an ongoing commitment, ethically, must be understood as a part of the sustainable development concept, since it allows, among others, the prevention of future risks, such as environmental impacts or litigation. It should be noted that sustainable development consists of three pillars, which are: social, environmental and economic; if harmony and integration between them, are not checked, there is an imbalance that directly reflects on the quality of life of the species, besides affecting the activities and business decisions, as these will depend on many factors that go far beyond the ways of obtaining financial gain. Therefore, adjust the company´s activities to the concept of sustainable development is a matter of survival rather than competitiveness. Thus, both state power as the private power complement each other and do not overlap when they have common goals that, in this specific case, are the preservation and maintenance of an ecologically balanced environment. Although the corporate social responsibility is not expressed exhaustively in the legislation, when analyzing the concept of sustainable development it will be clear that the inclusion of social and environmental responsibility is a duty to be taken by the companies and can not be understood as mere effective means of minimizing the advances in environmental legislation, considering that should be considered in a complementary manner.
A inserção da responsabilidade social no conceito de desenvolvimento sustentável, por sua vez, está abrangido de forma implícita no art. 225 da Constituição Federal de 1988 (CF/88). Cumpre mencionar que o constituinte elencou o meio ambiente equilibrado como um direito fundamental, decorrente do próprio direito à vida, sendo defeso qualquer atividade que potencialmente possa comprometer aquele - o bem ambiental protegido. Desta feita, a responsabilidade social, assumida pelas empresas como um compromisso contínuo, de forma ética, deve ser entendida como parte integrante do conceito de desenvolvimento sustentável, uma vez que possibilita, entre outros, a prevenção de riscos futuros, como impactos ambientais ou processos judiciais. Ressalte-se que desenvolvimento sustentável compõe-se de três alicerces, quais sejam: social, ambiental e econômico; caso não seja verificada uma harmonia e a integração entre ambos, existirá um desequilíbrio que refletirá diretamente na qualidade de vida das espécies, além de afetar as atividades e as decisões empresariais, visto que dependem de vários fatores que vão muito além das formas de obtenção de lucro financeiro. Portanto, adequar as atividades da empresa ao conceito de desenvolvimento sustentável é uma questão de sobrevivência e não de competitividade. Assim, tanto o poder estatal quanto o poder privado se complementam e não se sobrepõem quando possuem objetivos comuns que, no caso em tela, são a preservação e a manutenção de um meio ambiente ecologicamente equilibrado. Com efeito, embora a responsabilidade social das empresas não esteja expressa de forma taxativa na legislação, ao se analisar o conceito de desenvolvimento sustentável, clara estará a inserção da responsabilidade social e ambiental como um dever a ser assumido pelas empresas, não podendo ser compreendida como mero meio eficaz de minimização dos avanços da legislação ambiental, haja vista que devem ser analisada de forma complementar.
Keywords: Direito; Recursos naturais - Conservação; Desenvolvimento sustentável; Responsabilidade social da empresa; Ética empresarial; Responsabilidade (Direito); Conservation of natural resources; Sustainable development; Social responsibility of business; Business ethics; Liability (Law)